Diagnostic accuracy and clinical utility of the PHQ-2 and GAD-2: a comparison with long-format measures for depression and anxiety - Hlynsson, Jón Ingi; Carlbring, Per (Frontiers in Psychology, 2024)
Background Anxiety and depression are highly prevalent and often comorbid mental disorders that are encompassed within the broad category of emotional disorders. The frequent comorbidity of anxiety and depression can pose challenges for accurate diagnosis and treatment which, in turn, highlights the need for reliable measurements that are simultaneously responsive to change and prevent non-response bias. Brief measures of anxiety and depression can potentially increase response rates due to their brevity and ease of administration. This study evaluates the psychometric characteristics, discriminative accuracy, and sensitivity to change of the Generalized Anxiety Disorder 2-item scale (GAD-2) and the Patient Health Questionnaire 2-item scale (PHQ-2) within a clinical population. Method The sample comprised treatment-seeking participants (n = 3,411), screened (n = 2,477) to receive an internet-based psychotherapeutic intervention (cognitive-behavioral, psychodynamic, or waitlist). Results Brief measures can effectively detect individuals who may be eligible for a diagnosis of depression and anxiety, not only prior to but also during and following the completion of psychological treatment. The discriminative ability of the GAD-2 was significantly greater during active treatment and at post-assessment compared with pre-treatment screening, although no such differences were found for the PHQ-2. Finally, endorsing the most severe response option on the GAD-2 and PHQ-2 was associated with a high probability of presenting with clinically relevant anxiety and depressive symptoms. Conclusion Brief measures of anxiety and depression are viable instruments to screen for and monitor anxiety and depressive symptoms. Clinical trial registration ClinicalTrials.gov, identifier NCT05016843.